The Influence of Religiosity, Age, and Income on Willingness Volunteer for Indonesian Philanthropic Institutions - Fiqri, Alfany Arga Alil; Widiyanti, Dwi Retno (Review of Islamic Economics and Finance, 2023)
Purpose – This study aims to determine the influence of religiosity, age, and income on a Muslim's willingness to volunteer for philanthropic institution in Indonesia.Methodology - The variables in the study, Muslim's willingness to volunteer for philanthropic institution, religiosity, age, and income utilized the multinomial logistic regression as the analysis method. This research is conducted by using data from the World Value Survey Wave 7; while the sample used for this study was 351 respondents of Indonesian Muslim. Findings - The analysis found that the variables of religiosity, age, and income had a significant effect on a person's willingness to volunteer for philanthropic institutions in Indonesia. The respondent who has a higher level of religiosity tends to be an active member of Indonesian philanthropic institutions, and the respondent who has a lower level of religiosity tends to be a passive member.